RECENT ADVANCEMENT IN PERIODONTAL REGENERATION: AN UPDATE (International Journal of Food and Nutritional Sciences, 2023)
Periodontal diseases pose a significant challenge to oral health globally, necessitating the continuous exploration of innovative therapeutic strategies. Over the past decade, significant advancements have been made in periodontal regenerative therapies, offering promising avenues for the restoration of periodontal tissues. This comprehensive review synthesizes recent research findings and clinical developments in periodontal regeneration, encompassing various biomaterials, growth factors, and tissue engineering approaches. Key topics covered include the application of novel scaffolds, such as bioactive ceramics and polymers, in facilitating cell attachment, proliferation, and differentiation within periodontal defects. Additionally, the utilization of growth factors, such as platelet-derived growth factor (PDGF) and bone morphogenetic proteins (BMPs), to enhance periodontal tissue regeneration is discussed. Furthermore, emerging techniques in tissue engineering, such as cell-based therapies and gene therapy, are examined for their potential in promoting periodontal tissue regeneration. By critically evaluating the efficacy, safety, and clinical applicability of these regenerative approaches, this review provides valuable insights into the current landscape of periodontal regenerative therapies. Ultimately, these advancements hold promise for improving the outcomes of periodontal treatment and addressing the unmet needs in managing periodontal diseases.